Systematic review of the incidence of inferior alveolar nerve injury in bilateral sagittal split osteotomy and the assessment of neurosensory disturbances. Issue 4 (April 2015) - Agbaje, J.O.; Salem, A.S.; Lambrichts, I.; Jacobs, R.; Politis, C.
Abstract Extreme variation in the reported incidence of inferior alveolar nerve (IAN) disturbances suggests that neurosensory disturbances after orthognathic surgery have not been evaluated adequately. Here we review the reported incidence of IAN injury after orthognathic surgery and assess recently reported methods for evaluating sensory disturbances. A search was conducted of the English-language scientific literature published between 1 January 1990 and 31 December 2013 using the Limo KU Leuven search platform. Information on various aspects of assessing IAN injury was extracted from 61 reports. In 16 reports (26%), the incidence of injury was not indicated. Preoperative IAN status was not assessed in 22 reports (36%). The IAN assessor was described in detail in 21 reports (34%), while information on the training of the assessors was mentioned in only two reports (3%). Subjective evaluation was the most common method for assessing neurosensory deficit. We conclude that the observed wide variation in the reported incidence of IAN injury is due to a lack of standardized assessment procedures and reporting. Thus, an international consensus meeting on this subject is needed in order to establish a standard-of-care method.